Biomechanical Assessment of Torsional Stiffness in a Supracondylar Humerus Fracture Model. Issue 3 (March 2019) - Wallace, Melissa; Johnson, David B.; Pierce, William; Iobst, Christopher; Riccio, Anthony; Wimberly, R. Lane
Abstract : Background: We assessed the effect on the torsional stability by different pin diameters and varied pin configurations in a biomechanical supracondylar humerus fracture model. Methods: After scanning a model of a pediatric humerus, the image was imported into software. Variable pin trajectories were planned. Acrylonitrile butadiene styrene plastic models were 3-dimensionally printed with predetermined pin trajectories. Models were osteotomized and potted with a polyurethane resin. Five-pin configurations were designed to test coronal and sagittal patterns of pin placement. Each included 3 lateral pins and a medial pin. Pin diameters of 1.6, 2.0, and 2.4 mm were tested in all configurations. Three models for each pin diameter/configuration were tested to ensure uniformity. Stability of the construct was tested to determine the torque needed to deflect the osteotomy 10 degrees in internal/external rotation. Each model was tested 3 times. Results: In all models/configurations, the 2.4 mm pin diameter was statistically stiffer than 1.6 mm diameter pins; this lost statistical significance in certain patterns when comparing 2.0- and 2.4-mm pins. When comparing a divergent to a parallel configuration in the coronal plane, there was no significant difference in stability when pin diameter or number were controlled. The convergent pin configuration was, in general, the least stable pattern. Use of a medial pin conferred statistically significant stiffness throughout most models as demonstrated with pin deletion. Use of 2 pins was significantly less stiff than most 3-pin models. Conclusions: Larger pin diameters confer greater stiffness among all patterns. The use of 3 lateral and 1 medial pin was not statistically different than 2 lateral and 1 medial pin in our models. Both patterns were stiffer than 3 lateral pins only or other fewer pin constructs. The alignment of pins in the sagittal plane did not affect overall construct stiffness.